Map-based communication: a pivotal function of knowledge information in sports - Davi Sofyan; Khairul Hafezad Abdullah; Abdullah Yavuz Akinci; Ejiro Uriri Osiobe; Centurion Chandratama Priyatna (Jurnal Kajian Komunikasi, 2022)
Previous studies vividly indicate that understanding sports communication in competitive and non-competitive contexts could benefit athletes, coaches, officials, businesses, governing bodies, and spectators. This study aimed to inspect publication trends relevant to the global evolution of sports communication based on two high-impact and predominant databases, Scopus and Web of Science. The study analyzed selected top publications (peer-reviewed articles, books, and reports), keywords, and institutional data via ScientoPy on map-based communication. Our results depicted that the Scopus and WoS databases reveal growing trends in sports communication. The study's primary contribution is that it identified: the primary map-based communication research, essential keywords, connected studies, and leading universities within the sport management and sports scholarly fields. Keywords like (but not limited to) "public relations" and "organizational communication" has become prevalent in sport mapping communication between 2018 and 2019. The five most popular keywords concerning sports communication in include (but are not limited to) "Sports," "Communication," "social media," "Sports communication," and "Media." the findings of our paper will be helpful (but not limited to): scholars interested in sports communication, athletes (professional, non-professional, and students), stakeholders, and researchers. Similarly, the study provides future readers and scholars with a global perspective on the current hot topics in sports communication to help them disseminate their ideas, as well as a variety of analyses to assist in the organization of data and the development of theory and practice in sports communication research.